المباحث الأصولية في مؤلفات علوم القرآن - عبد المجيد حجاج; د/محمد رضا شوشة (جامعة عمار ثليجي الاغواط, 2023)
يعد الإمام بدر الدين الزركشي من العلماء الأفذاذ الذين لهم باع في العلوم والتصانيف في جميع الميادين، إلا أن شهرته في الد ا رسات القرآنية والأصولية أكثر م ن غيرها. والغاية من هذه الد ا رسة هي الوقوف على جانب من المباحث المشتركة بين العلمين؛ في مباحث دلالات الألفاظ باعتبار الخفاء والوضوح. ولقد خ صصت للمسائل المشتركة في مبحث المجمل والمبين، ومبحث الظاهر والمؤول؛ بين كتاب البرهان في علوم الق آ رن للزركشي ومؤلفات الأصوليين، والمقارنة بينها من ناحية التأليف، وكيفية تناولها بالبحث، وكذا المقارنة بينها من ناحية منهج بحثها، مع تبيين أثر هذه المباحث في استنباط الأحكام الشرعية . الكلمات المفتاحية: المباحث الأصولية، الزركشي، البرهان في علوم القرآ ن Abstract of the search Imam Badr al-Din al-Zarkashi is considered one of the distinguished scholars who have excelled in various fields of knowledge and authorship. However, his reputation is particularly prominent in Quranic and jurisprudence studies. The objective of this study is to explore one of the shared aspects between these two disciplines, specifically in terms of the implications of semantic expressions, considering both ambiguity and clarity. This research has been dedicated to the common issues discussed in the topic of general and specific principles of Islamic jurisprudence. It includes an examination of the books of The Proof in The Sciences of The Qur’an by Al-Zarkashi and jurisprudents books along with a comparison between them in terms of composition and their approach to research. Furthermore, it explores the comparative methodology employed in these studies in addition to highlighting their impact on the derivation of Islamic legal rulings. Keywords: jurisprudence studies. Al-Zarkashi. The Proof in The Sciences of The Qur’an